092 Mental health intervention for children with epilepsy (MICE): intervention development. (December 2018) - Walji, F; Welch, A; Smith, J; Bennett, S; Cross, H; Henderson, C; Heyman, I; Moss-Morris, R; Ross, J; Evans, A; Shafran, R
Abstract : Background: At least half of young people with epilepsy also have mental health problems such as depression, anxiety and behavioural difficulties. However, many children with epilepsy do not access the mental health treatments they need, in part because epilepsy services are separate from mental health services. Aims: To take an existing evidence-based mental health treatment (Modular Approach to Therapy in Children – MATCH) with established efficacy in children and young people and make changes to ensure it is relevant to children and young people with epilepsy. The aim is for the psychological therapy to be fully integrated with physical healthcare, delivered within epilepsy services over the telephone in a way that is sustainable for the NHS. Method: Advisory groups of young people with epilepsy and their families and epilepsy professionals discussed ways to ensure that the intervention was suitable for the specific needs of children with epilepsy and their families. We used the feedback from these groups and from previous patients, together with previous research to make small changes to the intervention in an iterative process using Plan-Do-Study-Act (PDSA) cycles. Normalisation Process Theory (NPT) was used as a framework to guide discussion and intervention development. Results: An epilepsy-specific module was added to the intervention. We also integrated some epilepsy-specific examples of difficulties throughout the remainder of the manual. Few changes were needed to the existing intervention, as families' main priority was that it was delivered flexibly with a focus on their own individual goals for treatment. Conclusion: Feedback from families and professionals is key in ensuring that therapies meet the needs of those they are designed to support and this study demonstrates that it complements knowledge of theory and the evidence-base. PDSA cycles together with NPT can be used as a framework to support the development of such interventions.